Critique and Fiction: Doing Science Right in Rural Education Research - Craig Howley (Journal of Research in Rural Education, 2009)
This essay explains the relevance of fiction to the practice of rural education research, in so doing engaging questions about the nature and purposes of research and, therefore, of science itself. Although many may assume science and fiction (in this account, novels) harbor contrary purposes and devices, this essay argues that, to the contrary, such a view damages research efforts. This damage is palpable in rural education research because of the meanings inherent in rural lifeways. Fiction provides a route to the critique needed to engage rural questions with authenticity and, therefore, with objectivity. Disregard of critique is nonetheless the official standard in education research. The argument here is thus widely applicable throughout education practice, research, and theorizing precisely because critique remains an alien concept in mainstream education research. The essay explains why critique is both important and overlooked, how novels contribute to critique in rural education research, and how to do critique relevant to empirical research.